Effect of Silver Nanowire Dimension to Ammonia Adsorption of Graphene-silver Nanowires Hybrid - Hoa, Huynh Tran My; Thu, Hoang Thi; Phuong Ha, La Phan; Phuong, Le Ha; Trung, Tran Quang; Thuan, Nguyen Van; Dinh, Nguyen Nang; Hanh, Phan Minh (Communications in Physics, 2014)
In this report, we study the effect of silver nanowires (AgNws) dimension to electrical properties of rGO/AgNws hybrid. The alteration of these electrical properties leads the difference of ammonia sensibility of the rGO/AgNws hybrid based sensing devices. When the rGO is accompanied by AgNws of different sizes from \(\sim 500$~\text{nm to } >10\;μ\)m, the ammonia sensitivity of these hybrids change from 60% to 340% alteration compared with the bare rGO material.